2019
DOI: 10.3390/jmse7120456
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Self-Burial Mechanism of Pipeline with Spoiler under Steady Flow Conditions

Abstract: Herein, hydraulic model experiments and numerical simulations were performed to understand the self-burial mechanism of subsea pipelines with spoilers under steady flow conditions. First, scour characteristics and self-burial functions according to the spoiler length-to-pipe diameter ratio (S/D) were investigated through hydraulic experiments. Further, the Navier-Stokes solver was verified. The experimental values of the velocity at the bottom of the pipeline with a spoiler and the pressure on the sand foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
4
7
0
1
Order By: Relevance
“…The corresponding results shown in Figure 9 confirm again that a spoiler with a larger length leads to a deeper scour depth beneath the pipeline. This observation is consistent with the results given by Lee et al [18], who found that a longer spoiler leads to a deeper scour depth with L/D = 0, 0.3 and 0.5, respectively. Based on the present numerical results, a quadratic polynomial function relationship is found between the scour depth and the spoiler length as follows: Figure 8 shows the numerical results of the local scour profile around the pipeline without and with a spoiler at t = 3000 s. It can be seen that although the scour profile does not change much for a pipeline with and without a spoiler, the scour range and the scour depth increase with the increase of the spoiler length.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The corresponding results shown in Figure 9 confirm again that a spoiler with a larger length leads to a deeper scour depth beneath the pipeline. This observation is consistent with the results given by Lee et al [18], who found that a longer spoiler leads to a deeper scour depth with L/D = 0, 0.3 and 0.5, respectively. Based on the present numerical results, a quadratic polynomial function relationship is found between the scour depth and the spoiler length as follows: Figure 8 shows the numerical results of the local scour profile around the pipeline without and with a spoiler at t = 3000 s. It can be seen that although the scour profile does not change much for a pipeline with and without a spoiler, the scour range and the scour depth increase with the increase of the spoiler length.…”
Section: Resultssupporting
confidence: 93%
“…The corresponding results shown in Figure 9 confirm again that a spoiler with a larger length leads to a deeper scour depth beneath the pipeline. This observation is consistent with the results given by Lee et al [18], who found that a longer spoiler leads to a deeper scour depth with L/D = 0, 0.3 and 0.5, respectively. Based on the present numerical results, a quadratic polynomial function relationship is found between the scour depth and the spoiler length as follows:…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…그 밖에 경계요소법 (Cho et al, 2013)과 유한차분법 (Kweon et al, 2014) 을 이용하여 SHP의 수리성능을 분석하기도 하였다. (Hayatdavoodi et al, 2017;You et al, 2019;Xu et al, 2019 (Lee et al, 2016b;Lee et al, 2018;Lee et al, 2019b;Lee et al, 2019c) 에서 여러 검증을 통해 확인된 바 있다.…”
unclassified